Saguaro (Carnegiea gigantea) Mortality and Population Regeneration in the Cactus Forest of Saguaro National Park: Seventy-Five Years and Counting - Orum, Thomas V.; Ferguson, Nancy; Mihail, Jeanne D. (PLOS ONE, 2016)
Annual census data spanning seventy-five years document mortality and regeneration in a population of saguaro cactus (Carnegiea gigantea) in the Cactus Forest of the Rincon Mountain District of Saguaro National Park near Tucson, AZ. On 6 four-hectare plots, each saguaro was censused and a methodical search for new saguaros was conducted annually each year from 1942 through 2016, with the exception of 1955. Regeneration has been episodic with 828 plants established from 1959 through 1993 compared with 34 plants established between 1942 and 1958 and only three plants established after 1993. The years preceding 1959 and following 1993, include some of the driest decades in centuries in southern Arizona. While woodcutting and cattle grazing are believed to be among the causes of decades of failed regeneration prior to 1958, neither of these factors contributed to the failed regeneration following 1993. The height structure of the population from 1942 to 2016 shifted dramatically from a population dominated by large saguaros (> 5.4 m tall) in the first three decades of the study to a population dominated by small saguaros (< 1.8 m tall) in the most recent two decades. Mortality is shown to be strongly age dependent. In the year following the 2011 catastrophic freeze, 21 of 59 plants older than 80 years died compared with zero deaths in 270 plants between the ages of 29 and 80 years. Saguaros under 40 years old, growing under small shrubs or in the open, have a lower probability of survival than better protected saguaros. Long-term population monitoring is essential to understanding the complex impacts of human and environmental factors on the population dynamics of long-lived species.